Photoirradiation of Polycyclic Aromatic Hydrocarbons with UVA Light – A Pathway Leading to the Generation of Reactive Oxygen Species, Lipid Peroxidation, and DNA Damage - Yu, Hongtao (2006)
Polycyclic aromatic hydrocarbons (PAHs) are a class of genotoxic environmental contaminants. We have long been interested in determining the mechanisms by which PAHs induce genotoxicity. Although the metabolic activation of PAHs leading to biological activities has been well studied, the photo-induced activation pathway has seldom reported. In this paper, we review the study of photoirradiation of PAHs with UVA irradiation results in (i) cytotoxicity and DNA damage (ii) DNA single strand cleavage; (iii) formation of 8-hydroxy -2′-deoxyguanosine adduct (8-OHdG), and (iv) formation of lipid peroxidation. Evidence has been shown that these photobiological activities are mediated by reactive oxygen species (ROS).